COMPARATIVE ANALYSIS OF ESG REPORTING STANDARDS IN CENTRAL ASIA: CHALLENGES AND OPPORTUNITIES FOR HARMONIZATION - Tukhtosheva Ezoza Farmon qizi; Tulakova Yulduz Odil qizi (European Science Publishing, 2025)
Environmental, Social, and Governance (ESG) reporting is increasingly important for attracting investment and demonstrating corporate responsibility. This paper conducts a comparative analysis of the current state of ESG reporting standards and practices in Central Asian countries. It identifies key differences in the adoption and implementation of various international frameworks, such as GRI, SASB, TCFD, and the UN Sustainable Development Goals (SDGs). The paper explores the challenges to widespread ESG reporting in the region, including data availability, regulatory gaps, lack of expertise, and awareness among businesses. Furthermore, it examines the opportunities for harmonization of ESG standards across Central Asia to improve comparability, attract foreign investment, and promote sustainable development. The analysis considers the potential role of regional organizations, government policies, and capacity-building initiatives in facilitating greater ESG transparency and accountability. The paper concludes with recommendations for policymakers and businesses to strengthen ESG reporting frameworks and promote sustainable practices in Central Asia.
Keywords: ESG Reporting, Environmental, Social, and Governance, Sustainability, Central Asia, GRI (Global Reporting Initiative), SASB (Sustainability Accounting Standards Board).